Sintesis Katalis Basa Padat Nanomagnetik CaO/Serbuk Besi Untuk Reaksi Transesterifikasi Minyak Sawit Off Grade Menjadi Biodiesel - Hafiz, Fadlillahi; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Nanomagnetic solid base catalyst synthesized with iron powder nanoparticle to load calcium oxide through impregnation method. The optimum conditions for the manufacture of catalysts investigated. Effect of weight ratio of CaO to iron powder and calcination temperature on the catalytic performance were studied. The catalyst with the highest activity is obtained when the weight ratio of CaO to iron powder is 80:20 and calcination temperature of 850 °C under transesterification reaction conditions of a molar ratio of methanol/oil 10:1, catalyst dosage of 1% by weight, temperature of 70 °C for 2 hours with biodiesel results reached 81.32%. CaO, Fe2O3 and Ca(OH)2 material was found in the catalyst through x-ray diffraction with a catalyst alkalinity values of H_ > 9.3 through alkalinity analysis using hammet indicator phenolphthalein and specific surface area of catalyst is 1.963 m2/g through Brunauer-Emmett-Teller (BET) analysis.Keywords: biodiesel, calcination, calcium oxide, catalysts, impregnation, iron powder, transesterification.